Patient care pathways under the model of integrating tuberculosis service with general hospitals in China. Issue 11 (8th October 2013) - Wei, Xiaolin; Yin, Jia; Zou, Guanyang; Walley, John; Zhong, Jiemign; Chen, Songhua; Sun, Qiang; Wang, Xiaoming
Abstract: Objective: To report care pathways of tuberculosis (TB) patients under the integrated model, where TB clinical service is provided by a general hospital instead of the TB dispensary, with the aim of providing policy recommendations for TB care reforms in China. Methods: Six counties implementing the integrated model were randomly selected, and 50 TB patients in each county participated in a questionnaire survey. Results: Of the 301 participants, 82 visited only the TB designated hospital. A patient visited a median of two health providers in total. The median external provider delay and internal provider delay were 1 and 0 day, respectively. The median out‐of‐pocket medical costs were US379 in total; US293 in the TB units and US0 in other health units in the TB designated hospital. Logistic regression analyses suggested that patients who visited the primary care facilities first tended to have longer external delays (OR = 5.71) than patients who visited the other hospitals (OR = 10.16). Conclusion: The integrated model is promising as it reported relatively fewer patient pathways and shorter delays than the dispensary model. However, the integrated model did not reduce patient out‐of‐pocket costs.